Mosquitoes and people. The territories of malaria in Tori-Bossito (Southern Benin) - (:unkn) unknown (My University, 2010)
One of the specificity of African sub-Saharan countries like Benin lies in their sub-tropical climate, warm and humid. Those climatic characteristics allow the existence of an endemic malaria transmission. However, at a micro-scale, different people are not exposed similarly to this health risk. Therefore, we wanted to understand which environmental characteristics (in a broad sense) were determinant for the malaria transmission at this very fine scale. We conducted a study in a rural district of southern Benin, Tori-Bossito, composed of nine villages. A territorial diagnosis, combined with an epidemiological survey of a cohort of 600 new-born, and with catches of anopheles vectors during the 3 years of the study (2007-2010), allowed the identification of i) the areas were the vectors was predominant, and ii) the vulnerability factors of people. The fieldwork consisted in collecting multi-scale environmental indicators (regional and local), and conducting a human geography analysis concerning bed nets and insecticides utilization practices, structure of habitat, and soil occupation close to the life places. By modeling these environmental variables into a GIS (Geographic Information System), we were able to show that a "territorialisation" of the risk in Tori-Bossito was present, associated with ethnic and socio-economic conditions. A spatial segregation linked to life-conditions that questions the vulnerability of people in a context of rural-urban migrations.
Keywords: African Research